2014
DOI: 10.1080/13218719.2014.959156
|View full text |Cite
|
Sign up to set email alerts
|

Service Users' Experiences of Voluntary Admission to Mental Hospital: A Review of Research Literature

Abstract: Australia and New Zealand are committed to upholding the rights of people who experience mental illness and providing a "recovery" approach to service delivery. These have farreaching implications for acute inpatients, many of whom are admitted voluntarily. In order to inform future research in these two countries, this review aimed to identify literature pertaining to the experiences of people admitted voluntarily to acute adult mental health facilities. Literature was limited to studies in English published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The concept of perceived coercion is not restricted to involuntarily admitted service users, with previous studies reporting up to 48% of voluntarily admitted service users describing levels of perceived coercion comparable to that of involuntarily admitted service users (Prebble et al, 2014). Voluntary patients who are treated on locked wards and those with more severe symptoms are more likely to have higher levels of perceived coercion , while those who are more satisfied with their treatment feel less coerced .…”
Section: Introductionmentioning
confidence: 93%
“…The concept of perceived coercion is not restricted to involuntarily admitted service users, with previous studies reporting up to 48% of voluntarily admitted service users describing levels of perceived coercion comparable to that of involuntarily admitted service users (Prebble et al, 2014). Voluntary patients who are treated on locked wards and those with more severe symptoms are more likely to have higher levels of perceived coercion , while those who are more satisfied with their treatment feel less coerced .…”
Section: Introductionmentioning
confidence: 93%
“…Also, the patient has privileged access to these end results, while the compulsion used should be readily available to staff. Some forms of compulsion, such as the legal status, are not always known by the patient (Prebble, Thom, & Hudson, 2015).…”
Section: The Conceptualization Of Experienced Coercion and The Appraimentioning
confidence: 99%
“…Service users focused on making contact, recovery and prevention of crisis in a safe environment with a person who is trusted by the user. This is confirmed in almost all the systematic reviews (Carstensen et al, 2017;Nugteren et al, 2016;Prebble et al, 2015;Wood & Alsawy, 2016). The need for -contact‖ resonates in the wish for collaborative and inclusive care, positive relationships, and a safe and therapeutic hospital environment (Wood & Alsawy, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, more attention has been given to the experiences of service users in psychiatric emergency wards. Most studies are conducted by academic researchers on users to gain an insight into their experiences in the acute emergency department of a psychiatric hospital or general emergency department of a hospital (Carstensen et al, 2017;Harris et al, 2016;Nugteren, Hafsteinsdóttir & Kool, 2016;Prebble, Thom & Hudson, 2015;Wood & Alsawy, 2016). For example, Nugteren et al (2016) showed in a systematic review that users experience inappropriate use of the ward rules, nurses' lack of time for interacting with patients, the feeling of humiliation, and lack of involvement of significant others in acute and closed psychiatric wards.…”
Section: Introductionmentioning
confidence: 99%